The relationship between self-determined motivation, emotional involvement, cognitive involvement and leisure-time physical activity among college students - Peng-fei Yang; Shao-wen Qian (Heliyon, 2024)
Objective: Grounded in self-determination theory and the stimulus-organism-response framework, this study examines factors that affect college students’ leisure-time physical activity by considering the basic psychological needs satisfaction (i.e., autonomy, competence, and relatedness), self-determined motivation, emotional and cognitive involvement. Methods: The sample included 526 students (47.8 % male; 57.2 % female) from four universities in central China. A structural equation model was used to analyze associations among variables. Results: The satisfaction of all three basic psychological needs had a significant positive impact on emotional involvement. Additionally, autonomy and competence need satisfaction had a significant positive impact on self-determined motivation and cognitive involvement. However, contrary to our expectation, there was no significant effect of relatedness need satisfaction on self-determined motivation and cognitive involvement. Furthermore, emotional involvement was found to have a significant effect on leisure-time physical activity intention for male students. Interestingly, the relationship between cognitive involvement and leisure-time physical activity intention is significant, but this effect was observed only among female students. Conclusion: Pedagogical strategies and tactics better satisfied students’ psychological needs, promote physical education classes emotional and cognitive involvement, therefore, achieve autonomous active lifestyle behaviors in leisure time.